2018
DOI: 10.1530/jme-17-0319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormones on thermogenesis and energy partitioning

Abstract: 21Thyroid hormones (TH) are of central importance for thermogenesis, energy homeostasis, 22and metabolism. Here we will discuss these aspects by focussing on the physiological 23 aspects of TH-dependent regulation in response to cold exposure and fasting which will be 24 compared to alterations in primary hyper-and hypothyroidism. In particular, we will 25 summarise current knowledge on regional thyroid hormone status in the central nervous 26 system (CNS) and in peripheral cells. In contrast to hyper-and hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 129 publications
(20 reference statements)
1
38
0
1
Order By: Relevance
“…Elevated glucocorticoid and thyroid hormone levels, and decreased leptin levels may contribute to the rapid cancellous bone loss observed in male and female mice housed at room temperature. Glucocorticoids, thyroid hormone and leptin are important regulators of bone metabolism and their levels are altered by housing temperature (62)(63)(64)(65)(66)(67)(68)(69). Further research is required to establish the role of changes in these hormones in premature cancellous bone loss in mice housed at sub-thermoneutral temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated glucocorticoid and thyroid hormone levels, and decreased leptin levels may contribute to the rapid cancellous bone loss observed in male and female mice housed at room temperature. Glucocorticoids, thyroid hormone and leptin are important regulators of bone metabolism and their levels are altered by housing temperature (62)(63)(64)(65)(66)(67)(68)(69). Further research is required to establish the role of changes in these hormones in premature cancellous bone loss in mice housed at sub-thermoneutral temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone signaling takes place peripherally, mostly in the liver, white and brown adipose tissues, but also centrally, in the hypothalamus [1,2]. Thyroid hormones directly stimulate energy expenditure changing the functionality and increasing the expression of genes involved in thermogenesis, such as uncoupling protein 1, in peripheral tissues such as skeletal muscle and brown adipose tissue (BAT), but also through central actions [3].…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to decreased temperatures, cold‐sensitive thermoreceptors activate the sympathetic nervous system (SNS), stimulating the release of norepinephrine, resulting in downstream lipolysis and release of free fatty acids. CE also results in decreases in triiodothyronine (T3) in the brain, further exciting the SNS and inhibiting the agouti‐related peptide neurons, an effect linked to decreases in appetite and EI, which has been previously explained in more detail . Conversely, peripheral T3 increases with CE, resulting in increases in thermogenesis.…”
Section: Cold Exposure Circulating Appetite‐related Peptides and Thmentioning
confidence: 93%
“…CE also results in decreases in triiodothyronine (T3) in the brain, further exciting the SNS and inhibiting the agouti‐related peptide neurons, an effect linked to decreases in appetite and EI, which has been previously explained in more detail . Conversely, peripheral T3 increases with CE, resulting in increases in thermogenesis. Studies in a variety of rodent species found significant increases in norepinephrine turnover, plasma norepinephrine, or urinary norepinephrine following a CE stimulus between 3 and 6°C.…”
Section: Cold Exposure Circulating Appetite‐related Peptides and Thmentioning
confidence: 93%